A Case of Thanatophoric Dysplasia Type I with Fetal Hydrops in the First Trimester - Giannina Calongos; Masateru Hori; Mai Ogino; Hideaki Sawai (Hindawi Limited, 2016)
During a routine prenatal exam, a 36-year-old female in her third pregnancy was diagnosed with fetal hydrops at 11 weeks of gestation. The pregnancy was monitored with periodic ultrasounds; however, spontaneous resolution was not observed. Amniotic fluid examination at 16 weeks of gestation showed a normal karyotype; however, macrocephaly, a narrow thorax, and shortening of the long bones were observed on ultrasonography. With the strong suspicion of a fetal skeletal disease, specifically thanatophoric dysplasia (TD), and after extensive genetic counseling, termination of the pregnancy was performed per the parents' wishes with mechanical cervical dilation and gemeprost (PGE1) administration. Following delivery, the fetus was found to have macrocephaly, a narrow bell-shaped thorax, and a protuberant abdomen, as well as curved long bones, H-shaped platyspondyly, and curved clavicles on skeletal radiography. As a result, the fetus was diagnosed with TD type I. This case illustrates that although TD is a rare disease, an accurate prenatal diagnosis can be made with the use of ultrasonography.